Expertise development at work : a workplace curriculum perspective in the domains of sales representatives and leadership coaches in a German context - Köhler, Daniel Paul [Verfasser]; Goller, Michael [Verfasser] (My University, 2024)
„Active engagement and participation in professional practices are an important requirement for expertise development in vocational domains. However, not much is known about how work contexts foster or hinder such expertise development. To further fill this research gap, this study investigates two vocational domains, namely sales representatives and leadership coaches, using the Workplace Curriculum Approach. This approach focuses on three aspects. First, how novices get access to certain tasks. Second, which tasks at work are especially conducive to learning, referred to as pedagogically-rich activities. Third, what knowledge is hard-to-learn through practice alone. By focusing on these three aspects, the Workplace Curriculum Approach helps to understand learning.“ (authors‘ abstract; BIBB-Doku)
Keywords: P 3.3 Führungskräfte; 370; Führungskraft; Trainer; Vertrieb; Kaufmännischer Beruf; Lernen am Arbeitsplatz; Lernförderliche Arbeitsgestaltung; Kompetenzentwicklung; Fachwissen; Interview